Optimization of Process Parameters and Culture Medium for L-(+)-Lactic Acid Production by Rhizopus oryzae - Bulut, Sule; Elibol, Murat; Ozer, Dursun (Soc Chemical Eng Japan, 2009)
The influence of process parameters such as carbon source, initial pH, agitation rate, inoculum size and fermentation temperature on L-(+)-lactic acid production by Rhizopus oryzae were examined in shaken culture. The highest lactic acid concentration of 62 g/L was obtained at 150 g/L glucose concentration, initial medium pH 6, agitation rate 150 rpm, inoculum size 1 x 10(8) spores/mL and fermentation temperature 32.5 degrees C. The maximum lactic acid concentration of 112 g/L was obtained at an agitation rate of 500 rpm and aeration of 0.75 vvm under optimum conditions found in the shake flask experiments in a 1-L stirred tank bioreactor in batch system. The oxygen transfer characteristic of the lactic acid production process was analyzed. Increases in both the agitation rate and the aeration rate increased the k(L)a values, with the agitation rate increase being much more effective. The effects of different fed-batch methods were determined. The constant feed rate fed-batch culture was an effective method for the production of lactic acid, the concentration of which reached 134 g/L, 19.6% higher than in the batch fermentation.
Keywords: Lactic Acid; Rhizopus oryzae; Process Parameters; Optimization; Fed-Batch Fermentation; Oxygen Transfer